2018
DOI: 10.1186/s12875-018-0865-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heart failure and other comorbidities on mortality in patients with chronic obstructive pulmonary disease: a register-based, prospective cohort study

Abstract: BackgroundMultimorbidity has already become common in primary care and will be a challenge in the future. Primary care in Sweden participates to a great extent in the care of patients with two severe, chronic conditions: chronic obstructive pulmonary disease (COPD) and heart failure. Both conditions are characterized by high mortality and often coexist. Age, sex, heart failure and other comorbidities are considered to be the major predictors of mortality in patients with COPD. We aimed to study the impact of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…Demographic variables from the SRTR comprise age and gender. Patient-related variables concern airway obstruction, measured by FEV 1% after bronchodilation if available, otherwise without bronchodilation, as well as oxygen saturation, number of exacerbations, and number of hospital admissions due to COPD in the last 12 months, BMI, which was categorized as <22, [22][23][24][25][26][27][28][29][30], and >30 kg/m 2 , and comorbidity. Patient-reported variables comprised smoking, exercise activity, measured by reported number of days with physical activity per week, and functional dyspnea, measured using the modified Medical Research Council (mMRC) Dyspnea Scale.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic variables from the SRTR comprise age and gender. Patient-related variables concern airway obstruction, measured by FEV 1% after bronchodilation if available, otherwise without bronchodilation, as well as oxygen saturation, number of exacerbations, and number of hospital admissions due to COPD in the last 12 months, BMI, which was categorized as <22, [22][23][24][25][26][27][28][29][30], and >30 kg/m 2 , and comorbidity. Patient-reported variables comprised smoking, exercise activity, measured by reported number of days with physical activity per week, and functional dyspnea, measured using the modified Medical Research Council (mMRC) Dyspnea Scale.…”
Section: Methodsmentioning
confidence: 99%
“…8,9 These multimorbidities were associated with higher health care costs, ED visits, mortality, and readmissions. [10][11][12] Readmission serves as one important indicator measuring the quality and utilization of expensive inpatient care that adds to total health care costs. In 2012, due to a trend of increasing inpatient total charges for 30-day COPDrelated readmissions, 13 the Centers for Medicare and Medicaid services (CMS) initiated the Hospital Readmissions Reduction Program (HRRP).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research reported that male and female patients were different in terms of COPDrelated 30-day readmission. 7,11,19 Males were more likely to be readmitted, 19,20 whereas females had fewer comorbidities and might be undertreated for COPD, itself. 21 Although gender plays an important role in COPD readmission, few studies have navigated how gender might affect the COPD-related 30-day readmission rate among patients with and without additional comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The cost-sternal and cost-vertebral joints are more rigid and calcified in patients with COPD than people without the disease [4,45]. Due to their respiratory condition, these patients have difficulty remaining on their backs for 20-30 minutes at a time and are often associated with heart failure and dyspnea [46]. As described earlier in this article, the rib cage is rigid, in an inspiratory attitude and shows postural changes [2].…”
Section: Amlpm and Copd: Can We Do Better?mentioning
confidence: 78%